2020
DOI: 10.21873/invivo.12126
|View full text |Cite
|
Sign up to set email alerts
|

Combining Radiomics and Blood Test Biomarkers to Predict the Response of Locally Advanced Rectal Cancer to Chemoradiation

Abstract: Background/Aim: A noninvasive method for predicting a patient's response to neoadjuvant chemoradiotherapy (nCRT) for locally advanced rectal cancer would be useful because this would help determine the subsequent treatment strategy. Two types of noninvasive biomarkers have previously been studied, based on radiomics and based on blood test parameters. We hypothesized that a combination of both types would provide a better predictive power, and this has not previously been investigated. Patients and Methods: Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This finding aligns with the previous report that radiomics features add value when combined with qualitative MRI features [20] while most studies did not provide such comparison. However, some studies have reported clinicopathological scores outperforming models that incorporate radiomics features [35].…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with the previous report that radiomics features add value when combined with qualitative MRI features [20] while most studies did not provide such comparison. However, some studies have reported clinicopathological scores outperforming models that incorporate radiomics features [35].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, pretreatment imaging biomarkers may have a role in predicting genomic profile. Some of the published radiomics studies on colorectal cancer mainly focused on chemoradiation response (12)(13)(14) or the related prognostic factors (11), and only a small number of studies performed their investigation on CT imaging modality. Yang et al (9) developed a support vector machine (SVM) model based on 346 radiomic features derived from pretreatment contrast-enhanced CT.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been evaluated to predict genotype or phenotype in breast cancer (3), renal cell carcinoma (4), glioma (5), and advanced or metastatic solid tumors treated with immunotherapy (6). In colorectal cancer, several studies have investigated the radiogenomic approach with various imaging modalities to predict KRAS mutation (7)(8)(9)(10), prognosis (11), and treatment response (12)(13)(14). Most imaging modalities of those studies were rectal MRI or PET for accurate tumor segmentation.…”
mentioning
confidence: 99%
“…The nomogram demonstrated accurate prediction of a GR and non-GR in both training and validation cohorts with AUC values of 0.970 and 0.949, respectively. In another study conducted in a single center, Jeon et al [86] developed a clinical-radiomics model based on T2WI images and blood biomarkers with an AUC of 0.785, which effectively distinguished between patients who did and did not achieve a GR. Additionally, according to Jeon et al [86], both blood biomarkers and radiomics features provide useful information for prediction, with the latter having a higher relative predictive power.…”
Section: Radiomics In Gr Predictionmentioning
confidence: 99%